Analysis of Leadership Styles and Organizational Commitment on Employee Performance with Organizational Citizenship Behavior as an Intervening Variable at the Insan Cemerlang Bondowoso Foundation - Niqmah, Fauziyah; Sularso, Raden Andi; Tobing, Diana Sulianti K. (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to analyze the styles of leadership and organizational commitment to employee performance through OCB at the Insan Cemerlang Bondowoso Foundation. The sampling method uses nonprobability sampling with all members of the population being sampled as many as 70 people. The research uses path analysis method with the SPSS application. The results show that leadership stylesand organizational commitment have a significant effect on OCB. The level of leadership styleswill have an influence on employee performance. A high level of organizational commitment will improve the performance of Insan Cemerlang Foundation employees, to achieve successful performance. The result shows that organizational citizenship behavior influences employee performance. Organizational citizenship behavior works as an intervening variable between the influence of leadership styleson employee performance. Organizational citizenship behavior also plays a mediating role between organizational commitment and employee performance.